2008
DOI: 10.1029/2007sw000345
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the space weather modeling framework using ground‐based magnetometers

Abstract: [1] Geomagnetically induced currents (GICs) can disrupt power grid operations, causing significant interference for many people; therefore, predictions of ground-based magnetic perturbations and their time derivatives are quite important. This study quantifies how well the University of Michigan's Global MHD code predicts approximately 150 ground-based magnetometer traces for a number of storm-time intervals. It is found that in order to accurately represent the magnetic perturbation, Biot-Savart integrals ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 17 publications
1
76
1
Order By: Relevance
“…This means that BATSRUS is a useful tool when studying different regimes within the solar system. As this study shows, and other validation studies have shown, BAT-SRUS is capable of accurately modeling the magnetospheric dynamics (e.g., Wang et al, 2008b;Yu and Ridley, 2008;Taktakishvili et al, 2007;Wang et al, 2008a;Welling and Ridley, 2010a;Yu et al, 2010). Further, BATSRUS is versatile enough that it can be used to simulate the magnetosphere under a wide variety of user needs (i.e., resolution, run-time, etc.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This means that BATSRUS is a useful tool when studying different regimes within the solar system. As this study shows, and other validation studies have shown, BAT-SRUS is capable of accurately modeling the magnetospheric dynamics (e.g., Wang et al, 2008b;Yu and Ridley, 2008;Taktakishvili et al, 2007;Wang et al, 2008a;Welling and Ridley, 2010a;Yu et al, 2010). Further, BATSRUS is versatile enough that it can be used to simulate the magnetosphere under a wide variety of user needs (i.e., resolution, run-time, etc.…”
Section: Discussionmentioning
confidence: 92%
“…Figure 12 shows the most relevant solar wind and IMF inputs into the MHD code that were used as a time-dependent upstream boundary condition on the MHD simulation as it ran. The studies by Yu and Ridley (2008); Wang et al (2008b) and Welling and Ridley (2010a) show many validation results of this time period that demonstrate how the code compares against other data sets not shown here.…”
Section: Time-dependent Simulationsmentioning
confidence: 99%
“…Ground magnetic field perturbations are calculated from Hall currents over the entire hemisphere by Biot-Savart integral, using the technique described by Yu and Ridley (2008). Figure 4 shows the ground perturbations at various magnetic local times and latitudes.…”
Section: Ground Signaturesmentioning
confidence: 99%
“…The simulated Dst index is calculated by the global magnetosphere model as the average value of the B z component of the magnetic field taken over a spherical surface at R = 3.0 R e . The simulated Dst index neglects the effect of currents inside 3 R e , but it still provides a reasonable approximation for the global magnetic perturbation (see Yu and Ridley [2008] for a detailed discussion). Finally, the in situ magnetic field values are obtained by interpolating the magnetic field from the global magnetosphere grid to the position of the satellite as it moves along its trajectory.…”
Section: Magnetic Storm Simulationsmentioning
confidence: 99%